Whole‐blood cytokine secretion assay as a high‐throughput alternative for assessing the cell‐mediated immunity profile after two doses of an adjuvanted SARS‐CoV‐2 recombinant protein vaccine candidate. Issue 1 (11th January 2022) - De Rosa, Stephen C; Cohen, Kristen W; Bonaparte, Matthew; Fu, Bo; Garg, Sanjay; Gerard, Catherine; Goepfert, Paul A; Huang, Ying; Larocque, Daniel; McElrath, M. Juliana; Morris, Daryl; Van der Most, Robbert; et al.
Abstract: Objectives: We previously described the Phase I‐II evaluation of SARS‐CoV‐2 recombinant protein candidate vaccine, CoV2‐PreS‐dTM, with AF03‐ or AS03‐adjuvant systems (ClinicalTrials.gov, NCT04537208). Here, we further characterise the cellular immunogenicity profile of this vaccine candidate using a whole‐blood secretion assay in parallel to intracellular cytokine staining (ICS) of cryopreserved peripheral blood mononuclear cells (PBMCs). Methods: A randomly allocated subset of 90 healthy, SARS‐CoV‐2‐seronegative adults aged ≥ 18 years who had received (random allocation) one or two separate injections (on study day [D]1 and D22) of saline placebo or CoV2‐PreS‐dTM formulated with AS03 or AF03 were included. Cytokine secretion was assessed using a TruCulture ® whole‐blood stimulation system in combination with multiplex bead array, and intracellular cytokine profiles were evaluated on thawed PBMCs following ex vivo stimulation with recombinant S protein at pre‐vaccination (D1), post‐dose 1 (D22) and post‐dose 2 (D36). Results: Both methods detected similar vaccine‐induced responses after the first and second doses. We observed a Th1 bias (Th1/Th2 ratio > 1.0) for most treatment groups when analysed in whole blood, mainly characterised by increased IFN‐γ, IL‐2 and TNF‐α secretion. Among participants aged ≥ 50 years, the Th1/Th2 ratio was higher for those who received vaccine candidate with AS03 versus AF03 adjuvant. ICS revealed that this higher Th1/Th2 ratio resulted from higher levels of IFN‐γ expression and that the vaccine induced polyfunctional CD4 + T cells. Conclusions: The whole‐blood cytokine secretion assay is a high‐throughput alternative for assessing the quantity and character of vaccine‐induced cellular responses. Abstract : Here, we characterise the cellular immunogenicity profile of a SARS‐CoV‐2 recombinant protein candidate vaccine, CoV2‐PreS‐dTM, formulated with AS03 adjuvant system or AF03 adjuvant, using a whole‐blood cytokine secretion assay in parallel to intracellular cytokine staining of cryopreserved peripheral blood mononuclear cells. Both methods detected similar vaccine‐induced responses after the first and second doses, with a Th1 bias observed for most treatment groups when analysed in whole blood. Among participants aged ≥ 50 years, a higher Th1/Th2 ratio was observed for participants who received vaccine candidate with AS03 than those who received AF03 adjuvant.